Seed yam production at GoSeed - Diebiru-Ojo, M. (YIIFSWA-II, 2020)
IITA GoSeed is a unit of the IITA Business Incubation Platform (BIP) and registered as a Limited Liability Company. The company saddled with the responsibility for the commercial promotion of the early generation seeds of the improved crop varieties generated by IITA and other CGIAR Centers across the globe